The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00422-010-0416-4
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent control: a computational theory of human control

Abstract: The paradigm of continuous control using internal models has advanced understanding of human motor control. However, this paradigm ignores some aspects of human control, including intermittent feedback, serial ballistic control, triggered responses and refractory periods. It is shown that event-driven intermittent control provides a framework to explain the behaviour of the human operator under a wider range of conditions than continuous control. Continuous control is included as a special case, but sampling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
328
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(340 citation statements)
references
References 71 publications
7
328
1
4
Order By: Relevance
“…Kleinman 1969) or an intermittent (e.g. Gawthrop et al 2011) model of control is more appropriate to explain the motor behaviour has been widely discussed in the literature. Results of the present study suggested that the control of movement was mainly continuous in young adults and mainly intermittent in older adults.…”
Section: Continuous Vs Intermittent Modelsmentioning
confidence: 99%
“…Kleinman 1969) or an intermittent (e.g. Gawthrop et al 2011) model of control is more appropriate to explain the motor behaviour has been widely discussed in the literature. Results of the present study suggested that the control of movement was mainly continuous in young adults and mainly intermittent in older adults.…”
Section: Continuous Vs Intermittent Modelsmentioning
confidence: 99%
“…During the last decades there have been found much evidence for a novel paradigm of human actions in balancing various systems-human intermittent control (for a review see, e.g., [1,2,3,4,5]). This paradigm implies that human control is discontinuous, repeatedly switching on and off instead of being always active throughout the process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the event-driven models have become widely employed [10,1,11,4]. They are built up on the fact that humans cannot detect small deviations of the controlled system from a desired state and for this reason are not able to control the system dynamics in its close proximity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations